1882 N.M. Laws 312-13 - (:unkn) unknown (My University, 1869)
Ch. 61, Deadly Weapons. Act of 1869, Ch. 32, §§ 1-3: Prohibited the carry of deadly weapons, including pistols, revolvers, derringers, repeaters, any other class of pistol, Bowie-knives, daggers, poniards, butcher knives, dirk-knives, cutting weapons, sword-canes, sharp-pointed canes, slung-shots, any other kind of deadly weapon. Punishable by not less than ten but no more than fifty dollars or not less than ten nor more than fifty days in jail or both.
Keywords: CARRY